(untitled) (Economics and region, 2021)
The article deals with the concept of production logistic management as a comprehensive and complementary category, the content of which is constantly enriched. The role of production logistic management for the development of enterprise activity is shown. The necessity of studying the cost-effective organization and management of material flows in a variable market environment should be based on the main principles of logistics. It is proved that organizations and operational management of material flows include a leading role in operational management of the organization, in the timely delivery of products and especially for increasing the efficiency of production associated with the use of production resources in time and space. It is substantiated that one of the key points of logistical management of the production organization is the planning of logistic capacities. The ratio of management of enterprise and logistic management are analyzed. It is emphasized the subordinate role of logistic management relative to the main goal of the organization (accelerating the movement of logistic streams). The main objectives of logistic supply, sales and production management are determined. Logistic management optimizes logistic decisions regarding the options between conflicting purposes based on the criterion of minimizing the integral expenses of the enterprise. Logistic management by its nature is a set of technical, technological, informational and socio-economic elements. Direct and backwards connections between them form a complex system of relations. The article proved that there is a need for the formation of a coordination center, which would manage the processes of integration of numerous material, information, labor and financial flows. Such a center is proposed to become a division of logistics in an enterprise aimed at detecting, calculations, optimization and planning of streaming processes at all levels. By organizing the movement of materials, information, frames and finances in a single process, the center reaches a decrease in the interruptions and expenses of production and economic and commercial activity. The logistic division of the enterprise, combining in one management complex of material and technical support, sales and transportation of goods, acquires significance that is not inferior to production.